A survey on mean glandular dose from full-field digital mammography systems, operate using Mo/Mo and W/Rh target/filter combinations - Jamal, Noriah; Abdul Hamid, Siti Selina; Samad Cheung, Humairah; Che Mohamed, Siti Kamariah; Muhammed Nordin, Ellyda; Hassan, Radhiana; Dahalan, Rehir (International Atomic Energy Agency, 2013)
We had conducted a survey on Mean Glandular Dose (MGD) from Full-Field Digital Mammography systems (FFDM) operate using Molybdenum/Molybdenum (Mo/Mo) and Tungsten/Rhodium (W/Rh) target/filter combinations. A survey was carried out at two randomly selected mammography centres in Malaysia, namely National Cancer Society and International Islamic University of Malaysia. The first centre operates using a W/Rh, while the second centre operates using an Mo/Mo target/filter combinations. On the basis of recorded information, data on mammographic views, MGD, age and Compressed Breast Thickness (CBT) were recorded for 100 patients, for each mammographic centre respectively. The MGD data were analyzed for variation with age group, with 5 years increment. The MGD data were also analyzed for variation with CBT, with 5 mm increment. We found that for both CC and MLO views, FFDM systems operated using Mo/Mo and W/Rh target/filter combinations present the same trend on MGD. The average MGD decreases as age increases. While average MGD increases with the increasing of CBT. However, FFDM system operates using Mo/Mo gives higher MGD as compared with FFDM system operates using W/Rh